Orientation-dependent production of normal Archimedean and dynamical spirals for revealing orbital symmetries in diatomic multi-orbital molecules - Harindranath B. Ambalampitiya; J. M. Ngoko Djiokap (Communications Physics)
Abstract The discovery and measurements of symmetric normal Archimedean spirals from atomic ionization by a pair of time-delayed broadband oppositely circularly polarized pulses revealed their potential of discerning orbital symmetry in atoms. Transferring this tool to molecules substantially increases experimental and theoretical challenges. Here, we show how Einstein’s photoelectric effect bypasses the congestion of electronic intermediate states and can access the orbital symmetry in heteronuclear, multi-orbital aligned molecules. Thanks to the broad bandwidth, multi-orbital ionization leads to multiplexed molecular-frame photoelectron momentum distributions, hiding thus any molecular orbital information. Only when molecular orientation is used to manipulate the ionization channels that one can identify a robust doorway into the molecular quantum world in which the asymmetry inherent to the highest-occupied molecular orbital can be unambiguously revealed by the asymmetric molecular spirals from single-color pulses. Our results demonstrate the potential of polarization-tailored attopulse sequences for the retrieval of spectroscopic details on molecular orbital symmetries.